Association of the combination of corporal adiposity and cardiorespiratory fitness with cardiometabolic risk factors in children — PREVOI Study - Renata Chácara Pires; Haysla Xavier Martins; Míriam Barbosa; Maria del Carmen Bisi Molina (Revista Paulista de Pediatria)
ABSTRACT Objective: To assess the association between the combination of corporal adiposity (CA) and cardiorespiratory physical fitness (CRF) with cardiometabolic risk factors in children aged 7–10 years. Methods: Cross-sectional observational study with a sample of 251 children registered in Family Health Units. Sociodemographic, lifestyle, anthropometric, biochemical, blood pressure, and CRF data were collected. Cardiometabolic risk factors assessed: total cholesterol, HDL-c, LDL-c, triglycerides (TG), fasting glucose and blood pressure. CRF was assessed by the 6-minute run/walk test and classified into: “physically unfit” and “physically fit”. Nutritional status was assessed by body mass index (BMI)/age and categorized into CA groups: “no excess weight [≤ z-score+1]” and “excess weight [> z-score+1]”. CRF and CA were combined, and the children were classified as “no excess weight + physically fit”, “no excess weight + physically unfit”, “excess weight + physically fit” and “excess weight + physically unfit”. Bivariate analyses were performed, and Poisson regression models were tested. The Statistical Package for the Social Sciences (SPSS) version 21.0 software was used, adopting p<0.05. Results: Around 65% of the children had low CRF and 59% had excess weight (overweight+obesity). After adjustment, there was a greater occurrence of having altered HDL-c, TG and presence of ≥ 3 grouped cardiometabolic factors among those who had excess weight + physically unfit. Conclusions: The prevalence of altered HDL and TG and of ≥3 grouped cardiometabolic risk factors was significantly higher among children who had excess weight and were physically unfit.